Spin-oï¬€ Policy on Islamic Insurance Industry Development in Indonesia: Maslahah Perspective - Waluyo, Agus (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2020)
This study aims to describe the eï¬€orts to develop the sharia insurance industry in Indonesia. This study is aÂ literature review supported by data and analysis with sources in the form of books, articles, websites andÂ documents. This study resulted in several ï¬ndings, including one of the eï¬€orts to develop the shariaÂ insurance industry was pursued by the government through a spin-oï¬€ policy. The spin-oï¬€ policyÂ normatively and substantially can encourage the growth of Islamic insurance in the country and inÂ accordance with the community expectations in actualizing beneï¬ts in order to protect religion, life,Â descent, reason and property. The sharia insurance spin-oï¬€ process in Indonesia has not run as expected.Â To support the acceleration of spin-oï¬€ policy realization, it must be supported by strengtheningÂ regulations and human resources, product innovation, literacy, and expanding access. The implication ofthis study is that there is still a need to strengthen regulations and human resources so that the shariaÂ insurance spin-oï¬€ policy program can be realized.